Flexible MISFET Devices From Transfer Printed Si Microwires and Spray Coating - Saleem Khan; Leandro Lorenzelli; Ravinder Dahiya (IEEE Journal of the Electron Devices Society, 2016)
This paper presents two types of metal insulator field effect transistors (MISFETs) devices fabricated from Si microwires through a new manufacturing route involving a combination of printing and microfabrication technologies. Si microwires, developed through standard photolithography and etching steps, are transferred from a silicon on insulator wafer onto polyimide using stamp-assisted transfer printing. The MISFETs are then obtained by spray coating the dielectric layer and metal contact layer. Spray coating has been introduced here for the first time for deposition of organic dielectric on transfer printed Si microwires. Two groups of the devices are fabricated, one based on a single Si microwire and the other based on the array of 15 microwires of similar dimensions. The variations in the output response of the two groups of devices has been investigated. The devices based on array of microwires are observed to have less variation in the output response, with lesser standard deviations as compared to MISFETs made from single Si microwires.